UV Spectrophotometric Estimation of Phenytoin Sodium in Pure and Pharmaceutical Formulations - A. Mantri, Mangesh; Shanmukhappa, S. (Asian Journal of Chemistry, 2010)
A simple, sensitive, spectrophotometric method in UV region has been developed for the determination of phenytoin sodium in bulk and tablet dosage form. Solution of phenytoin sodium in ethanol shows a maximum at 205 nm. Beer's law was obeyed in the concentration range of 2-14 μg/mL with 0.999 as the correlation coefficient value. The slope and y-intercept obtained for the curve was 0.061 and 0.014, respectively. Results of the analysis were validated statistically and by recovery studies (101.88 ± 1.33) Result of percentage recovery and placebo interference shows that the method was not affected by the presence of excipients, which proves suitability of the developed method for the routine estimation of phenytoin sodium in bulk and solid dosage form.